2008
DOI: 10.3944/aott.2008.272
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-intensity pulsed sound waves delivered by the Exogen device on Staphylococcus aureus morphology and genetics

Abstract: Low-intensity sound waves may be beneficial as a prophylactic measure to prevent infections in primary orthopedic operations and as an adjuvant therapy for infected nonunions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…The physical stress caused by cavitation decreased the stability of the bacterial outer membrane, then the bacterial membrane loosened after ultrasonic irradiation, and, consistent with previous study [22], the cellular walls appeared to be thicker than normal. Only in the G MUS group, discontinuity could be observed, a proof that MUS created a stronger cavitation than US alone.…”
Section: Discussionsupporting
confidence: 90%
“…The physical stress caused by cavitation decreased the stability of the bacterial outer membrane, then the bacterial membrane loosened after ultrasonic irradiation, and, consistent with previous study [22], the cellular walls appeared to be thicker than normal. Only in the G MUS group, discontinuity could be observed, a proof that MUS created a stronger cavitation than US alone.…”
Section: Discussionsupporting
confidence: 90%
“…Pornpongmetta and Thanut tamavong [16] reported microbial substrate utilization by aerobic bacteria from municipal waste water treat ment plant to be affected by music. Ayan et al [17] have shown that low intensity pulsed sound can affect morphology and genetics of Staphylococcus aureus.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier few reports [3,6,7,8,23] have indicated the ability of sound to influence microorganisms. Sound (whether in form of music or otherwise) can travel through the growth medium in which microbes are inoculated and this can give rise to vibrations.…”
Section: Resultsmentioning
confidence: 99%
“…Pornpongmetta et al [6] reported microbial substrate utilization of aerobic bacteria from municipal waste water treatment plant to be affected by music. Ayan et al [7] have shown that low-intensity pulsed sound can affect morphology and genetics of Staphylococcus aureus. Eukaryotic life forms have also been reported to be influenced by sound.…”
Section: Introductionmentioning
confidence: 99%